KAJIAN KUALITAS AIR SUNGAI SERUAI KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA UNTUK KEGIATAN BUDIDAYA IKAN - Adolf C Sinambela; Hasan Sitorus; Rusdi Leidonald (AQUACOASTMARINE, 2017)
River Seruai is one of the rivers in Deli Serdang District of North Sumatera, that has been polluted by human activities. Pollution that occurs can caused the decreased of river water quality. This study aimed to identify the suitability of water quality of River Seruai for freshwater aquaculture in order to improve fish farming in the river. The study was conducted from May 2017 to July 2017 along the River Seruai of Deli Serdang District of North Sumatra Province. The measurement of water quality parameters was done at 3 (three) stations. Based on the plankton abundance, it still be stated that the Seruai River was still support for fish farming activities because the river has plankton which was a source of natural food for aquaculture fish although the number is relatively low ie average 47.25 cells/liter. Scores of water quality parameter of River Seruai based on Standard Quality PP No. 82 of 2001 that the scor of 1st station = 0, score of 2nd = -2 and score of 3rd station = -2. The status of the water quality of each station I is in accordance with the quality standard, the 2nd and 3rd station is lightly contaminated. The overall status of River Seruai Water Quality has a score = 0. Based on PP No. 82 of 2001 it can be concluded that the waters were suitable for freshwater fish farming activities.Keyword : Water Quality, Aquaculture, River Seruai, Deli Serdang